Psychological Approach of Jadis’ Act of Violence in Novel Entitled Narnia: The Lion, The Witch, and The Wardrobe by C.S. Lewis - Grifian Azharinas; Bunayya Izzani; Wahyu Indah Mala Rohmana (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
This article presents a psychological analysis of Jadis, the White Witch, a character in the novel "The Lion, the Witch, and the Wardrobe" by C.S. Lewis. This research uses a qualitative approach, focusing on in-depth analysis methods regarding Jadis' characteristics and traits. By applying psychological theory, especially Freud's "Id" theory, this analysis highlights the motivations, emotions, and feelings that underlie Jadis's journey in the novel. The research findings highlight the complex psychological characteristics of these characters, including reluctance, anxiety, and social interactions with other characters. The goal is to provide a comprehensive picture of Jadis and encourage further research into her character and critical psychological analysis